KHIYĀR: MANIFESTASI KEADILAN EKONOMI ISLAM (KAJIAN HADIS RIWAYAT IBNU MĀJĀH NO. 2172) - Luthfiyah Amirah; Muh. Anugrah Isfa Arrasyi; Hukmiah Husain (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This research aims to describe the concept of Khiyār as an effort to realize economic justice in Islamic business. This research uses a literature study research method with a qualitative descriptive approach. The data sources of this research are primary data in the form of verses of the Qur'an and Hadith, as well as secondary data in the form of books and articles related to the focus of the research discussion. The results show that in the sale and purchase transaction there is Khiyār, which is a situation where consumers have the right to continue or cancel the sale and purchase if they feel unsuitable for the size/color of the goods, do not understand the usefulness of the goods and there are defects in the goods. Justice is created when both parties do not feel injustice, the seller is not oppressed by the buyer and the buyer does not feel oppressed by the seller. The right of Khiyār plays an important role in consumer protection and prevents unfair buying and selling practices. With Khiyār, economic justice can be realized by giving individuals the opportunity to make the best decision for themselves in order to achieve benefits and prevent regrets in the future. Khiyār is one of the proofs of how perfect Islam is in regulating a transaction so that both parties (seller and buyer) feel mutually satisfied with the contract they are carrying out, as Allah says in QS. An- Nisa'/4:29.